HUBUNGAN TERPAAN IKLAN SHOPEE SERTA TOKOPEDIA, AKSES APLIKASI DAN MINAT MEMBELI PADA MAHASISWA UNTAG SURABAYA - Fitri Norhabiba; Merry Fridha Tri Palupi; Afifatur Rohimah (Universitas Tidar, 2019)
The internet has brought many changes to society. As a new media, the internet not only has a function as a means of producing and distributing messages as other traditional media, but also as a media for storing messages. The convenience offered then developed into an application that makes it easy for users to be accessed at any time. Consumer behavior changes from traditional to online.This study examines aspects of the elaboration likelihood model and advertising exposure that are associated with consumer behavior for young people, especially at the student level and is a portrait contribution of a small proportion of young people in urban areas.This research took place in Untag Surabaya. The campus location was chosen because it is in the middle of the city and represents the profile of urban students for research. The population is Untag Surabaya students, amounting to 13849 students. Samples taken were 160 students, according to the calculation of Slovin formula, sampling by systematic random sampling. This type of research is quantitative descriptive in which data is taken to describe and generalize portraits of adolescent urban students.The results showed that there was a positive, moderate, and significant relationship between shopee advertising exposure and Tokedia, access to applications, and buying interest in Untag students, r (160) = 0.560 and 0.560, p <0.01. So it can be concluded that the higher exposure to Shopee and Tokedia advertisements, the higher the application access, the higher the buying interest.